1998
DOI: 10.3758/bf03201160
|View full text |Cite
|
Sign up to set email alerts
|

Flashbulb memories and the underlying mechanisms of their formation: Toward an emotional-integrative model

Abstract: Flashbulb memories (FBMs) are detailed recollections of the context in which people first heard about important events. The present study investigates three models of the formation and maintenance of FBM. Two models have previously been proposed in the literature (Brown & Kulik, 1977;Conway et al., 1994). A third model of FBM that integrates theories ofFBM and recent developments in the field of emotions is proposed. The present study compares these three competing models by investigating the FBMs that Belgian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
238
7
23

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(283 citation statements)
references
References 41 publications
15
238
7
23
Order By: Relevance
“…Moreover, previous studies have shown that both personal importance and rehearsal frequency -variables identified in the present study as being associated with NDE's intensity-are two variables playing a crucial role in the maintenance of vivid memories, such as "flashbulb memories" (e.g. Bohannon & Symons, 1992;Finkenauer et al, 1998;Wright & Nunn, 2000). It even appears that these variables are the two most significant factors that allow the differentiation of flashbulb and non-flashbulb memories (Tekcan & Peynircioğlu, 2002) -even more significant than other variables such as emotional valence or the surprise effect.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Moreover, previous studies have shown that both personal importance and rehearsal frequency -variables identified in the present study as being associated with NDE's intensity-are two variables playing a crucial role in the maintenance of vivid memories, such as "flashbulb memories" (e.g. Bohannon & Symons, 1992;Finkenauer et al, 1998;Wright & Nunn, 2000). It even appears that these variables are the two most significant factors that allow the differentiation of flashbulb and non-flashbulb memories (Tekcan & Peynircioğlu, 2002) -even more significant than other variables such as emotional valence or the surprise effect.…”
Section: Discussionmentioning
confidence: 52%
“…where they were when the event occurred, what they were doing) while NDE memories refer to memories of a personally lived experience classically occurring during a life-threatening situation. Nevertheless, it appears that, in both cases, the event seems to benefit from a preferential encoding that makes then them more details than other real or imagined events memories (for NDE memories: see Thonnard et al, 2013; for "flashbulb memories": see Finkenauer et al, 1998;Rubin & Kozin, 1984). Moreover, previous studies have shown that both personal importance and rehearsal frequency -variables identified in the present study as being associated with NDE's intensity-are two variables playing a crucial role in the maintenance of vivid memories, such as "flashbulb memories" (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The case study design was implemented due the number of variables that were considered: our study assessed event memory, flashbulb memory, as well as subjective reliving of flashbulb memories (i.e., vividness, rehearsal, emotion, surprise, novelty, and importance). The latter characteristics were implemented following research on flashbulb memories in normal subjects [20,[32][33][34] as well as the Autobiographical Memory Questionnaire [35] which was designed to evaluate autobiographical reliving. Because studies with long abstinence duration suggest that recovery or substantial improvements in memory functions can occur [7,[36][37][38], it would be of interest to assess whether flashbulb memories would trigger high recall as well as extensive reliving in alcohol abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a las bases teóricas que fundamentan este cuestionario, los autores acentúan los desarrollos en la investigación psicológica en torno a la evaluación cognitiva de las emociones (Moreira & Gamboa, 2016) y las consecuencias que dicha evaluación tendría en la formulación de un modelo de formación de las MFB. De nuevo, los autores no entregan un análisis detallado de las propiedades del instrumento, aunque cabe aclarar que las variables observables (aquellas que recoge la prueba) son la base para realizar los modelos de ecuación estructural que permiten finalmente a Finkenauer et al (1998) concluir que su modelo alcanza índices más aceptables para la explicación de la formación y mantenimiento de la MFB de la muerte del rey Baudouin comparado con los de Brown y Kulik (1977) y Conway et al (1994).…”
Section: Introductionunclassified
“…La prueba creada por Finkenauer et al (1998) es retomada y modificada por Er (2003) para postular un nuevo modelo de formación para las MFB basado en los recuerdos del contexto de recepción de la noticia del terremoto de Mármaraque afectó a Estambul, Kocaeli y otras regiones de Turquía en 1999. Luego de un análisis factorial exploratorio, el instrumento quedó conformado por 32 ítems.…”
Section: Introductionunclassified